A Novel Osteochondrodysplasia With Empty Sella Associates With a TBX2 Variant - Mäkitie, Riikka E.; Toiviainen-Salo, Sanna; Kaitila, Ilkka; Mäkitie, Outi (Frontiers in Endocrinology, 2022)
Skeletal dysplasias comprise a heterogenous group of developmental disorders of skeletal and cartilaginous tissues. Several different forms have been described and the full spectrum of their clinical manifestations and underlying genetic causes are still incompletely understood. We report a three-generation Finnish family with an unusual, autosomal dominant form of osteochondrodysplasia and an empty sella. Affected individuals (age range 24–44 years) exhibit unusual codfish-shaped vertebrae, severe early-onset and debilitating osteoarthritis and an empty sella without endocrine abnormalities. Clinical characteristics also include mild dysmorphic features, reduced sitting height ratio, and obesity. Whole-exome sequencing excluded known skeletal dysplasias and identified a novel heterozygous missense mutation c.899C>T (p.Thr300Met) in TBX2, confirmed by Sanger sequencing. TBX2 is important for development of the skeleton and the brain and three prior reports have described variations in TBX2 in patients portraying a complex phenotype with vertebral anomalies, craniofacial dysmorphism and endocrine dysfunctions. Our mutation lies near a previously reported disease-causing variant and is predicted pathogenic with deleterious effects on protein function. Our findings expand the current spectrum of skeletal dysplasias, support the association of TBX2 mutations with skeletal dysplasia and suggest a role for TBX2 in development of the spinal and craniofacial structures and the pituitary gland.